Comparison of Microscopic Interacting Boson Model and Quasiparticle Random Phase Approximation 0νββ Decay Nuclear Matrix Elements - Kotila, Jenni (Frontiers in Astronomy and Space Sciences, 2021)
The fundamental nature of the neutrino is presently a subject of great interest. A way to access the absolute mass scale and the fundamental nature of the neutrino is to utilize the atomic nuclei through their rare decays, the neutrinoless double beta ($0νββ$) decay in particular. The experimentally measurable observable is the half-life of the decay which can be factorized to consist of phase space factor, axial vector coupling constant, nuclear matrix element and function containing physics beyond the standard model. Thus reliable description of nuclear matrix element is of crucial importance in order to extract information governed by the function containing physics beyond the standard model, average neutrino mass in particular. Comparison of double beta decay nuclear matrix elements obtained using microscopic interacting boson model (IBM-2) and quasiparticle random phase approximation (QRPA) has revealed close correspondence, even though the assumptions in these two models are rather different. The origin of this compatibility is not yet clear, and thorough investigation of decomposed matrix elements in terms of different contributions arising from induced currents and the finite nucleon size is expected to contribute to more accurate values for the double beta decay nuclear matrix elements. Such comparison is performed using detailed calculations on both models and obtained results are then discussed together with recent experimental results.